Transforming Governance Through Information Access: A Strategy to Accelerate the Economic Development of Jayapura City - Silo, Akbar; Harikedua, Alfani Laura; Tupamahu, Shanty shinta (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the role of the Jayapura City Government in facilitating access to public information as a community-based development strategy, identify the community's critical capacity in responding to such information, and formulate a constructive interaction model to support local economic development within the context of Papua's Special Autonomy. Utilizing a descriptive qualitative approach supplemented by quantitative data from a survey of 165 respondents across five districts, the research finds that the Jayapura City Government has initiated a digital transformation through the Smart City program and the provision of various information infrastructures, such as Command Centers and free internet access in rural villages. The analysis reveals that a majority of the community (71.5%) perceives the government as moderately to highly active in disseminating development information, with 66.7% of respondents considering the information services relatively user-friendly and responsive. Despite these advancements, structural challenges such as the digital literacy gap and uneven internet access between regions, particularly in peripheral areas like the Muara Tami District, remain significant obstacles to creating inclusive and accountable information governance.